Application of golden ratio in increasing the appeal of proportions in design / Azmir Mamat Nawi ... [et al.] - Mamat Nawi, Azmir; Mohd Yusof, Wan Zaiyana; Mohd Yassin, Hafeezur Rahmaan (Universiti Teknologi MARA, Kedah, 2022)
The main objective of this paper is to assess the accuracy and proportionateness of logo design while maintaining the aesthetic value of the original logo design. For this study, the Phi Matrix Golden Ratio software was used to understand better and deepen the calculation of the proportion in the golden ratio in creating a logo. This software makes it possible to designate a precise proportion for the logo during the entire creation process. Local business will benefit from this research when it comes to creating company logos.